Physician Consultations, Prostate Cancer Knowledge, and PSA Screening of African American Men in the Era of Shared Decision-Making - Woods-Burnham, Leanne (Am J Mens Health, 2018)
African American (AA)/Black men are more likely to develop aggressive prostate cancer (PCa), yet less likely to be screened despite guidelines espousing shared decision-making regarding PCa screening and prostate-specific antigen (PSA) testing. Given the documented racial disparities in PCa incidence and mortality, engaging interactions with physicians are especially important for AA/Black men. Thus, this study evaluated occurrence of physician–patient conversations among AA/Black men, and whether such conversations were associated with PCa knowledge. We also quantified the serum PSA values of participants who had, and had not, discussed testing with their physicians. Self-identified AA/Black men living in California and New York, ages 21–85, donated blood and completed a comprehensive sociodemographic and health survey (n = 414). Less than half (45.2%) of participants had discussed PCa screening with their physicians. Multivariate analyses were used to assess whether physician–patient conversations predicted PCa knowledge after adjusting for key sociodemographic/economic and health-care variables. Increased PCa knowledge was correlated with younger age, higher income and education, and having discussed the pros and cons of PCa testing with a physician. Serum PSA values were measured by ELISA. Higher-than-normal PSA values were found in 38.5% of men who had discussed PCa screening with a physician and 29.1% who had not discussed PCa screening. Our results suggest that physician–AA/Black patient conversations regarding PCa risk need improvement. Encouraging more effective communication between physicians and AA/Black men concerning PCa screening and PSA testing has the potential to reduce PCa health disparities.